Active Flavonoids From Lagotis brachystachya Attenuate Monosodium Urate-Induced Gouty Arthritis via Inhibiting TLR4/MyD88/NF-κB Pathway and NLRP3 Expression - Ouyang, Xiang; Li, Na-Zhi; Guo, Min-Xia; Zhang, Man-Man; Cheng, Jie; Yi, Li-Tao; Zhu, Ji-Xiao (Frontiers in Pharmacology, 2021)
Lagotis brachystachya Maxim is a characteristic herb commonly used in Tibetan medicine. Tibetan medicine records it as an important medicine for the clinical treatment of "Yellow Water Disease", the symptoms of which are similar to that of arthritis. Our previous study showed that the flavonoid fraction extracted from Lagotis brachystachya could attenuate hyperuricemia. However, the effects of the active flavonoids on gouty arthritis remain elusive and the underlying mechanism is not understood. In the present study, the effects of the active flavonoids were evaluated in rats or Raw264.7 cells with gouty arthritis induced by monosodium urate (MSU) crystal, followed by the detection of TLR4, MyD88, pNF-κB and NLR family pyrin domain containing 3 (NLRP3) expression. The swelling of the ankle joint induced by MSU crystal began to be relieved 6 h post the administration with the active flavonoids. In addition, the active flavonoids not only alleviated MSU crystal-induced inflammation in synovial tissues by histopathological examination, but also reduced tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β) levels in the joint tissue fluid of MSU crystal-induced rats. Furthermore, western blot analysis indicated that the active flavonoids reduced the production of these cytokines by inhibiting TLR4/MyD88/NF-κB pathway and decreasing NLRP3 expression in synovial tissues of rats. More importantly, the inhibition of TLR4/MyD88/NF-κB pathway and NLRP3 expression was also confirmed in MSU-induced Raw264.7 cells. In conclusion, these results indicated that the active flavonoids from Lagotis brachystachya could effectively attenuate gouty arthritis induced by MSU crystal through TLR4/MyD88/NF-κB pathway and NLRP3 expression in vivo and in vitro, suggesting several potential candidates for the treatment of gouty arthritis.